Ethnicity and tax filing behavior - Spencer Bastani; Thomas Giebe; Chizheng Miao (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyze differences in tax filing behavior between natives and immigrants using population-wide Swedish administrative data, focusing on two empirical examples. First, controlling for a rich set of variables, we compare deduction behavior of immigrants and natives with the same commuting patterns within Sweden's largest commuting zone. We find that newly arrived immigrants file fewer deductions than natives, that immigrants with a longer duration of stay in the host country behave more like natives, and that immigrants with the longest stay file the most, even more than natives. Second, we analyze bunching behavior among the self-employed at the salient first kink point of the Swedish central government income tax schedule, located in the upper middle part of the income distribution. We find that self-employed immigrants exhibit significantly less bunching behavior than natives, even after a long time in the host country. We highlight residential segregation as a main driver of the observed behavioral differences.
Keywords: D31; H21; H24; H26; J22; J61; 330; deductions; tax filing; bunching; immigrants; natives; integration